Testing Function Focused Care for Acute Care using the Evidence Integration Triangle: Protocol description. Issue 3 (11th March 2022) - Resnick, Barbara; Boltz, Marie; Galik, Elizabeth; Kuzmik, Ashley; Ellis, Jeanette; Wells, Chris; Zhu, Shijun
Abstract: This manuscript provides the protocol for a National Institute of Aging‐funded cluster randomized clinical trial that focuses on helping nurses in acute care to engage patients with dementia in physical activity while hospitalized using an approach referred to as function‐focused care. Physical activity is defined as bodily movement produced by skeletal muscles resulting in the expenditure of energy and includes functional tasks such as bathing and dressing, leisure activity, ambulation, and moderate and vigorous intensity physical activity such as dancing, bike riding, or walking upstairs. The development of Function Focused Care for Acute Care (FFC‐AC) was based on the Social Ecological Model and Social Cognitive Theory and includes four steps: (1) Environment and Policy Assessments; (2) Education; (3) Establishing Patient Goals; and (4) Mentoring and Motivating of Staff (all levels of nursing staff), Patients, and Families. Function‐focused care activities include motivating older patients to participate in bed mobility; personal care activities such as bathing, dressing, ambulating as they are able; and other types of physical activities. The integration of the intervention among the nurses on the units is guided by the Evidence Integration Triangle (EIT), which includes the participation of a stakeholder team and practical outcome measures. The intervention is therefore referred to as FFC‐AC‐EIT. In addition to describing the protocol developed to test the effectiveness and feasibility of FFC‐AC‐EIT, a description of ways to overcome some of the barriers and challenges that can be encountered with this study is provided.